Analisis dampak layanan perpustakaan terhadap karir dosen: Studi terhadap ?dosen UIN Sunan Kalijaga Yogyakarta - Muh Khabib; Muchti Nurhidaya; Heru Pasuko Rini (IJAL (Indonesian Journal of Academic Librarianship), 2023)
The State of UIN Sunan Kalijaga Yogyakarta Library in accordance with its tagline become a "research partner" in providing reference sources for the academic community, one of which is lecturers. Lecturers in their career development are required to have scientific papers published in scientific journals. This study aims to determine whether the services provided by the library affect the careers of lecturers, especially in terms of providing referral sources. This research is quantitative descriptive research. This research was conducted at UIN Sunan Kalijaga Yogyakarta. The total population in this study was 744 people and the samples taken were 88 people who were drawn using a simple random sampling technique. Data collection using the questionnaire method. The validity test, reliability test, correlation test, and regression test used the IBM SPSS statistic 26 programs. The results showed that the library services of UIN Sunan Kalijaga Yogyakarta were in the very high category with a percentage score of 80, 39%. Meanwhile, the career of a lecturer at UIN Sunan Kalijaga Yogyakarta is in the good category with a percentage score of 74.78%. There is a relationship and influence between library services on lecturer careers at UIN Sunan Kalijaga Yogyakarta of 0.669 which is included in the strong category, this is indicated by the coefficient of determination of 44.1% and the remaining 55.9% is determined by other factors.